Аналгетична активність солей 2-(5-(адамантан-1-іл)-4-R-1,2,4-тріазол-3-ілтіо)оцтової кислоти - Одинцова, Віра Миколаївна; Одинцова, В. Н.; Odintsova, V. M. (Запорізький державний медичний університет, 2016)
Незважаючи на різноманітні підходи до терапії больового синдрому, котрі з розвитком медицини еволюційно змінюються й удосконалюються (а з ними й лікарські препарати, що застосовуються для лікування болю), залишаються значні складнощі у вирішенні цієї проблеми. Тому з метою виявлення серед синтезованих сполук тих, що здатні змінювати поріг больової чутливості дослідних тварин, вивчили дії солей 2-(5-(адамантан-1-іл)-4-R-1,2,4-тріазол-3-ілтіо)оцтової кислоти на центральний компонент ноцицептивної системи за умов термічного подразнення кінцівок щурів. Встановили закономірності відносно хімічної будови та фармакологічної дії похідних 1,2,4-тріазолу. Це свідчить про перспективність дослідження солей 2-(5-(адамантан-1-іл)-4-R-1,2,4-тріазол-3-ілтіо)оцтової кислоти як потенційних субстанцій для створення нових лікарських засобів на їхній основі. Несмотря на различные подходы к терапии болевого синдрома, которые с развитием медицины эволюционно меняются и совершенствуются (а с ними и лекарственные препараты, применяемые для лечения боли), остаются значительные трудности в решении этой проблемы. Поэтому с целью выявления среди синтезированных соединений тех, которые способны изменять порог болевой чувствительности подопытных животных, было изучено действие солей 2-(5- (адамантан-1-ил)-4R-1,2,4-триазол-3-илтио)уксусной кислоты на центральный компонент ноцицептивной системы в условиях термического раздражения конечностей крыс. Установлены закономерности относительно химического строения и фармакологического действия производных 1,2,4-триазола. Это свидетельствует о перспективности дальнейшего исследования солей 2-(5- (адамантан-1-ил)-4R-1,2,4-триазол-3-илтио)уксусной кислоты в качестве потенциальных субстанций для создания новых лекарственных средств на их основе. Despite the varied approaches to the pain syndrome therapy with the changes and improvements of evolutionary medicine’s development and the drugs which are used to treat pain there are still considerable difficulties in solving this problem. Aim. To detect compounds that are able to change the pain in experimental animals the action of salts of 2-(5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-ylthio)acetic acid on central component of the nociceptive system has been studied in terms of thermal irritation of the extremities of rats. Materials and results. First synthesized salts of 2-(5-(adamantane-1-yl)-4-R-1,2,4-triazole-3- ylthio)acetic acid have been used in studies. Analgesic activity has been determined on «a hot plate» model, based on the ability of studied substances to change the pain threshold of experimental animals in comparison with control and expressed in percents. Analgin was used as the comparison drug at a dose of 1000 mg/kg (Analgin-Darnitsa, solution for injections, 500 mg/ml, 2 ml in ampules № 10). Conclusions. The regularities between chemical structure and pharmacological action of 1,2,4-triazole derivatives have been determined. It testifies the prospects of further studies of salts of 2-(5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-ylthio)acetic acid, as potential substances to create new drugs.
Анальгетическая активность солей 2-(5-(адамантан-1-ил)-4R-1,2,4-триазол-3-илтио)уксусной кислоты
Analgesic activity of the salts of 2-(5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-ylthio)acetic acid
Keywords: анальгетики; адамантан; 1,2,4-тріазол; анальгетики; адамантан; 1,2,4-триазол; Analgesics; Adamantane; 1,2,4-triazole